Biochemical, Molecular, and Transcriptional Highlights of the Biosynthesis of an Effective Biosurfactant Produced by Bacillus safensis PHA3, a Petroleum-Dwelling Bacteria - Hanano, Abdulsamie; Shaban, Mouhnad; Almousally, Ibrahem (Frontiers in Microbiology, 2017)
Petroleum crude oil (PCO)-dwelling microorganisms have exceptional biological capabilities to tolerate the toxicity of petroleum contaminants and are therefore promising emulsifier and/or degraders of PCO. This study describes a set of PCO-inhabiting bacterial species, one of which, identified as Bacillus safensis PHA3, produces an efficient biosurfactant which was characterized as a glycolipid. FTIR, NMR, TLC, HPLC and GC-MS analysis of the purified biosurfactant revealed that the extracted molecule under investigation is likely a mannolipid molecule with a hydrophilic part as mannose and a hydrophobic part as hexadecanoic acid (C16:0). The data reveal that: i) PHA3 is a potential producer of biosurfactant (9.8±0.5 mg mL-1); ii) pre-adding 0.15% of the purified glycolipid enhanced the degradation of PCO by approximately 2.5 fold; iii) the highest emulsifying activity of biosurfactant was found against the PCO and the lowest was against the naphthalene; iv) the optimal PCO-emulsifying activity was found at 30-60° C, pH 8 and a high salinity. An orthologous gene encodes a putative -diglucosyldiacylglycerol synthase (-DGS) was identified in PHA3 and its transcripts were significantly up-regulated by exogenous PAHs i.e. pyrene and benzo(e)pyrene but much less by mid-chain n-alkanes and fatty acids. Subsequently, the accumulation of -DGS transcripts coincided with an optimal growth of bacteria and a maximal accumulation of the biosurfactant. Of particular interest, we found that PHA3 actively catalyzed the degradation of PAHs notably the pyrene and benzo(e)pyrene but was much less effective in the mono-terminal oxidation of n-alkanes. Such characteristics make Bacillus safensis PHA3 a promising model for enhanced microbial oil recovery and environmental remediation.